Calculation of thermophysical properties of oils and triacylglycerols using an extended constituent fragments approach - Cruz-Forero, Diana-Carolina; González-Ruiz, Oscar-Andrés; López-Giraldo, Luis-Javier (CT&F - Ciencia, Tecnología y Futuro, 2012)
This paper validates and implements an Extended Constituent Fragments methodology (ECF) for the calculation of thermophysical properties of vegetable oils considering the latter as triglyceride (TAG's) mixtures, both homogeneous and heterogeneous. For this purpose, three different vegetables oils were chosen (soybean oil, canola and olive) and their TAG's profiles were estimated using the ECN 42 generalized method. The ECF methodology estimates the properties of TAG's from their fragment composition and specific parameters of each property, which are adjusted using experimental information available in literature. The average relative errors of calculated properties were between 1 and 32% depending on the oil and the property. These errors were significantly lower than those obtained using the Aspen HYSYS commercial software, which oscillates between 70 and 100%. Additionally, by extrapolating the constituent fragments methodology a method for calculating boiling temperatures of TAG's with average relative errors of 1% was proposed. The calculations of properties for the ECF method were performed using the OIL-CALPROP software developed specifically for this purpose.